A hybrid lamination model for simulation of woven fabric reinforced thermoplastic composites solid-state thermo-stamping. (15th February 2021) - Deng, Tianzhengxiong; Zhang, Wentao; Jiang, Wei; Zhou, Helezi; Huang, Zhigao; Peng, Xiongqi; Zhou, Huamin; Li, Dequn
Abstract: Solid-state thermo-stamping of fabric reinforced composites has attracted extensive attention for its efficiency and potential energy saving in recent years. In this paper, a hybrid lamination model is proposed to describe the forming behavior of woven fabric reinforced thermoplastic composites (WFRTP) during solid-state thermo-stamping process. The woven carbon fiber (CF)/ Polyetheretherketone (PEEK) sheet/prepreg is modelled as laminate structure with woven reinforcement layers (shell elements) embedded in thermoplastic resin layer (solid elements). More specifically, a hypoelastic constitutive model is used to represent the anisotropic mechanical behavior of fabric reinforcement under large deformation, while the fabric model is calibrated and validated by uniaxial bias extension (UBE) test and tensile test of woven fabric. A phenomenological model is adopted to describe the viscoelastic-plastic deformation behavior of thermoplastic resin, while the resin model is calibrated by tensile tests of PEEK. The applicability of the hybrid model is demonstrated through comparing numerical results of UBE tests and Erichsen tests with their corresponding experiment results. The hybrid lamination model provides a theoretical foundation for numerical simulation of WFRTP solid-state thermo-stamping. Graphical abstract: Unlabelled Image Highlights: A hybrid lamination model based on embedded element technique was proposed. The lamination model allows for describing the solid-state thermo-stamping of woven fabric reinforced thermoplastic composites. The lamination model gives accurate prediction of shear angle and profile Experimental and predicted results of lamination model show that temperature is the key factor affecting the forming process.